Coping Mechanism of Family Caregiver to Handle Stress in Taking Care Dementia Patients: A Case Report - Upik Rahmi; Khoerunisa Amalia; Septian Andriyani; Lisna Anisa Fitriani; Suci Tuty Putri; Farida Murtiani; Aninda Dinar Widiantari (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: This study aimed to identify the burden, family caregiver reaction, and change of coping response reaction after caring for taking care dementia patient. Method: The study design used was a qualitative study report. The respondents were two caregivers who took care of mild-moderate dementia patients. We used the Revised Memory and Behavior Problems Checklist, Revised Ways of Coping Checklist (WCCL-R), and Caregiver Burden Inventory (CBI). We also did a pretest and posttest to respondents. The intervention was coping strategy given six times in two weeks. Results: We found decrease of burden of family caregivers, decrease of reaction to patients’s disturbing behavior and increased of coping of family caregiver. Conclusion:  We conclude that coping strategy affected on caregiver’s burden and reaction to declining cognitive aspect of patients. Coping strategy could reduce family caregivers’ burden in taking care dementia patients.